2018
DOI: 10.1107/s2053229618005740
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, evaluation of bioactivity and structure determination of amethinol A, a prototypic amethane diterpene from Isodon amethystoides bearing a six/five/seven-membered carbon-ring system

Abstract: We report the isolation of a novel diterpene, designated as `amethane', from Isodon amethystoides (Lamiaceae). The diterpene [amethinol A; systematic name: (4aR,4bR,7R,10aS)-4b,7-dihydroxy-7-isopropyl-1,1-dimethyl-9-oxododecahydrobenzo[a]azulene-4a(2H)-carboxylic acid], possesses a unique skeleton containing a six/five/seven-membered tricyclic system. Intermolecular O-H...O close contacts were found to the carboxyl, carbonyl and hydroxy groups, connecting molecules into a two-dimensional structure. A possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In addition, the observed NOSEY cross-peaks between H-7 and H-14β and between H-14β and H 3 -17 determined the co-facial relationship of the protons of H-7 and H 3 -17. The resulted Flack number of 0.07 (10) from the refinement of the X-ray crystallographic data on CuKα radiation allows the determination of the absolute configuration of 1 to be the same as an isopimarane diterpenoid (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the observed NOSEY cross-peaks between H-7 and H-14β and between H-14β and H 3 -17 determined the co-facial relationship of the protons of H-7 and H 3 -17. The resulted Flack number of 0.07 (10) from the refinement of the X-ray crystallographic data on CuKα radiation allows the determination of the absolute configuration of 1 to be the same as an isopimarane diterpenoid (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Previous phytochemical investigations of this species revealed significant differences in the chemical profiles of the secondary metabolites among the plants collected from various geographical areas [ 4 – 6 ]. Our recent research on a sample of this species collected from Libo County in Guizhou Province also led to the identification of a novel bioactive diterpene with 6/5/7 carbon skeleton, which showed inhibitory activity against the autoimmune disease-associated RORγt [ 10 ]. These prior findings encouraged us to carry out further phytochemical studies to discover additional new bioactive diterpenoids from this plant.…”
Section: Introductionmentioning
confidence: 99%
“…102 3.2.7 Amethinol A. Amethinol A, a diterpene isolated from Isodon amethystoides (Lamiaceae), was shown to possess inhibitory effects on RORgt at 10 mg ml À1 in a Gal4-based luciferase assay performed in Jurkat cells. 145 No further pharmacological information was provided by the authors.…”
Section: A-hydroxycholesterolmentioning
confidence: 99%
“…In recent years, many groups have studied the chemical composition and pharmacological activity of the Isodon plants, and have shown that they are rich in diterpenoids and have good biological activity including antibacterial, antitumor and immunosuppressive effects [5,6]. Thus it is necessary to investigate further examples of diterpenoids.…”
Section: Commentmentioning
confidence: 99%